Evaluation of agromorphological trait of rice landraces collected from Haor areas of the north-eastern part of Bangladesh (Journal of the Bangladesh Agricultural University, 2020)
Rice (Oryza sativa L.) is gifted with a lot of biodiversity both in the form of landraces and wild species. Rice breeders are working to evaluate genetic variability by digging out desirable characters and assessing them up to which extent they are heritable. Therefore, this study was carried out to know the presence of valuable agro-morphological traits in landraces of rice and to find out the landraces of rice having agronomic and genetic importance. The north-eastern part of Bangladesh is rich with wide range of land topography from hill, haor (backswamp), river and floodplain. This chorography of land renders continuous natural crossing, variation and evolution of land races of rice. In this study, different qualitative and quantitative traits of twenty promising rice landraces were evaluated. Data revealed that qualitative characters like leaf blade color and basal leaf sheath color was green until late vegetative stage in most of the cultivars which shows higher photosynthesis potentiality. Leaf angle, flag leaf angle was erect and awn was present in most of the cultivars which also reflect photosynthetic ability of the cultivar. Shattering percentage was low and seed coat color was brown in most of the cultivar indicating most of them are shattering loss resistant. On the other hand, panicle type was compact in most of the cultivars. Considering quantitative characteristics higher grain yield and yield attributes was recorded in the cultivars of Pajam, Changirmora, Jori, Kakhibiroin, Latma, Chinigura, and Chorabiroin. Moreover, some landraces of rice could be used as a source of potent genetic material.J Bangladesh Agril Univ 18(1): 76–85, 2020https://doi.org/10.5455/JBAU.72541